Самозванці історичних творів української й російської літератур першої половини ХІХ ст. - Ніколова, Олександра Олександрівна; Nikolova, Alexandra (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті виконано порівняльне дослідження образів самозванців у творах на історичну тематику українських (Г. Квітки-Основ’яненка, П. Куліша) та російських (О. Пушкіна, Ф. Булгаріна, О. Хомякова, О. Шишкова, М. Погодіна) письменників. Специфіку художньої інтерпретації самозванства розглянуто також у контексті європейської традиції.The article deals with the comparative study of impostors in historical works of Ukrainian (G. Kvitka-Osnovyanenko’s, P. Kulish’s) and Russian (A. Pushkin’s, F. Bulgarin’s, A. Khomyakov’s, A. Shishkov’s, N. Pogodin’s) literature. The subject of the study are images of historical persons who pretended to be kings (Gregory Otrepyev, Pugachev, Peter Chernyshov). Specificity of interpretation of this phenomenon seen in the context of the European tradition (Spanish, Italian, German drama). We are considering it in the aspects of ideological and esthetic principles of historical romanticism (interest in the extraordinary historical figures, trends of psychologization, ambiguous interpretation, amplification lyricism, dramatic effect), carnival-comic discourse (satirical ridicule, criticism of human and social disadvantages). We make a comparative analysis on the basis of synthesis of contact-genetic and typological methods. We make conclusions about the specifics of imagery concretization of imposture in Ukrainian and Russian literature in first half of the ХІХ-th centuries and its relationship with the thematic contexts.
Impostors of Historical Works of Ukrainian and Russian Literature in First Half of the ХІХ-th Centuries (in the Context of the European Tradition)
Keywords: самозванство; історизм; генетичні зв’язки; типологічні подібності; художня специфіка; imposture; historicism; genetic links; typological similarity; art specificity